Genetic Diversity and Population Differentiation of Naked Carp (Gymnocypris przewalskii) Revealed by Cytochrome Oxidase Subunit I and D-Loop - Fang, Di-an; Luo, Hui; He, Miao; Mao, Chengcheng; Kuang, Zhen; Qi, Hongfang; Xu, Dongpo; Tan, Longfei; Li, Yuandong (Frontiers in Ecology and Evolution, 2022)
Biodiversity in the Qinghai Lake of China is threatened by climate change, human activities as well as natural factors, affecting endangered Gymnocypris przewalskii, and eliciting conservation concerns. Thus, further research is necessary. In order to explore the genetic aspects of G. przewalskii, the genetic diversity, genetic structure and population differentiation of 566 representative individuals from seven geographically distinct ranges of Qinghai Lake were evaluated by mitochondrial DNA cytochrome oxidase subunit I (COI) and D-loop sequences. The content of A+T was higher than that of C+G for the above two molecular markers. Besides, estimates of genetic parameters showed that the seven populations of G. przewalskii had high levels of haplotype diversity (0.50243–0.94620) and low levels of nucleotide diversity (0.00079–0.00624). Haplotype genealogy indicated there was no obvious phylogenetic pattern between haplotypes. Both markers denoted the absence of population genetic structure. Furthermore, this work illustrated two simple, reliable and inexpensive molecular markers for analysis of genetic diversity, while the sensitivity of the mitochondrial D-loop region as a reflection of genetic diversity in G. przewalskii is higher than that of the COI gene.